2005
DOI: 10.1177/1359104505051213
|View full text |Cite
|
Sign up to set email alerts
|

Severely Impaired Young Refugees

Abstract: A B S T R A C TThis article is concerned with the small numbers of refugee children and adolescents who, for psychiatric reasons, have significant social impairment, with difficulties in functioning within their families and in school. Data from recent studies carried out in London are presented regarding the characteristics of this group. The studies show that the impaired refugee children are psychiatrically heterogeneous, but had high exposure to past violence and losses, and they experience high levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In general, similar to the current findings, there is evidence pointing to the fact that following the experience of a myriad of stressors from both their past and new life, refugee children are more prone to exhibit behavioural difficulties than non‐refugee children (Ehntholt & Yule, ; Hodes, , , ; Hodes & Tolmac, ; Howard & Hodes, ; Lustig et al ., ; Shallow & Whitington, ). Peer problems could be explained by the differences between the refugee and natives (e.g., ethnicity, educational level and language) whereby such differences could lead to discrimination, and poor peer relations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In general, similar to the current findings, there is evidence pointing to the fact that following the experience of a myriad of stressors from both their past and new life, refugee children are more prone to exhibit behavioural difficulties than non‐refugee children (Ehntholt & Yule, ; Hodes, , , ; Hodes & Tolmac, ; Howard & Hodes, ; Lustig et al ., ; Shallow & Whitington, ). Peer problems could be explained by the differences between the refugee and natives (e.g., ethnicity, educational level and language) whereby such differences could lead to discrimination, and poor peer relations.…”
Section: Discussionsupporting
confidence: 86%
“…Refugee children compared to other groups of vulnerable and at‐risk children are more prone to develop psychological disturbances (Bronstein & Montgomery, ; Fazel, Reed, Panter‐Brick, & Stein, ). Some studies have found that at the onset of migration, refugee children exhibit conduct problems and several social and behavioural problems, which may worsen during the process of migration (Hodes, , , ; Hodes & Tolmac, ). The loss of their native land can create a deep grievance, which could affect their mental health and their functioning (Betancourt et al ., ; Worthington, ), while relocation to a new unfamiliar environment can trigger a loss of self‐identification, sense of security, and well‐being (Mann, ; Worthington, ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to this group, it is remarkable that the asylum-seeking children battled more frequently with depression, anxiety and social anxiety than the children in youth care and had fewer problems with hyperactivity, aggression and anti-social behaviour. Because both the international literature (Andersson et al, 2005;Stein, 2002, 2003;Hodes and Tolmac, 2005;Hodes et al, 2008) and our study sample revealed that asylum-seeking children fairly often face internalizing behavioural problems, this constitutes the criterion in our prediction model.…”
Section: Sample Characteristicsmentioning
confidence: 94%
“…As a result, these children often struggle with behavioural problems (Bronstein and Montgomery, 2011;De Haene and Grietens, 2005;Derluyn and Broekaert, 2008;Kalverboer and Zijlstra, 2008a). Internalizing behavioural problems in particular, such as anxieties, depression, sleeplessness, nightmares, physical complaints and suicide are often reported among asylum-seeking children (Andersson, Ascher, Björnberg, Eastmond, and Mellander, 2005;Stein, 2002, 2003;Hodes, Jagdev, Chandra, and Cunniff, 2008;Hodes and Tolmac, 2005). We will therefore focus the question about the predictive value of the BIC-Q upon this type of problem as a criterion.…”
Section: Introductionmentioning
confidence: 97%
“…A second important factor reflects the ability of children to remember the details of what they have been told or the sequence of events that have happened to them (Larsson and Lamb 2008). A significant number of studies show that whilst asylum‐seeking children are psychiatrically heterogeneous, many have high exposure to high levels of violence and disruption in their lives, past violence and losses, and they experience high levels of isolation compared with non‐refugee peers (Hodes 2005). The journey itself can entail trauma, fear and uncertainty (Hopkins and Hill 2008).…”
Section: ‘It Just Makes Me Feel Bad’: the Realities Of Current Practicementioning
confidence: 99%